THE PRIVATE CONSULTANCY IN EDUCATION MANAGEMENT AT CAMPINAS EDUCATION PUBLIC SYSTEM - Sara Badra de Oliveira (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This article aims at contributing to the comprehension of current managerial reforms that reconfigure the public administration. Within the agreement signed in 2013 between the Municipality of Campinas and Comunitas organization, we analyze specifically the work plan of Falconi Company in articulation with the Municipal Education System, and its proposal of providing a results-based management consultancy. At the same time, this Education System has been implementing a Participatory Institutional Assessment Policy, which intends to be an alternative to managerial policies, in the wake of societal public administration. The article makes a documentary analysis of the private consultancy proposal, place it in a broader context of the Third Way strategies, and discuss to what extent the participation of partner organizations in the management of Campinas educational policy represents a "sum of efforts" in order to improve education, or a confrontation with the logic of participation advocated by Participatory Institutional Assessment Policy. Keywords: Private Consultancy. Education Management. Institutional Assessment. Participation. Managerialism.